The effect of logical-mathematical intelligence on mathematics learning and moderator analysis: A meta-analysis - Onesimus Laia, Harun; Martadiputra, Bambang Avip Priatna; Dahlan, Jarnawi Afgani (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study explores the contribution of logical-mathematical intelligence to students' mathematics learning and investigates whether certain contextual factors act as moderators of this relationship. Method: A meta-analysis was conducted by synthesizing findings from empirical studies published between 2014 and 2024. The research followed a systematic review protocol using the PRISMA method, selecting only quantitative studies that focused on the relationship between logical-mathematical intelligence and variables in mathematics education. Data from eligible studies were analyzed using meta-analytic software to estimate effect sizes and assess the influence of various moderator variables, including educational level, sample size, year of publication, and geographical context. Findings: The results demonstrate a strong and consistent relationship between logical-mathematical intelligence and mathematics learning. Students with higher levels of this intelligence tend to perform better in understanding concepts, solving problems, and achieving learning goals in mathematics. While the influence of this intelligence appears stable across different educational levels and locations, notable variations were found based on the sample sizes of the included studies. Significance: The findings emphasize the essential role of logical-mathematical intelligence in mathematics education. Educators are encouraged to integrate teaching strategies that nurture this intelligence through problem-based learning, logical reasoning activities, and concept visualization tools. This study also calls for future research to explore additional moderating factors, such as gender or teaching style, to gain a more nuanced understanding of how this form of intelligence interacts with diverse learning environments.